COMPLEX QUALITY INDICATOR OF SUGARS AND SUGAR SUBSTITUTES AND THEIR USE IN THE PRODUCTION OF CONFECTIONERY PRODUCTS - Antonella DOROHOVYCH (Stefan cel Mare University of Suceava, 2018)
The paper presents the results of calculation on the basis of the basic principles of theoretical qualimetry of the complex index of quality of sugars and sugar substitutes. When evaluating sugars according to the complex indicator as the differential indicators, there were selected sweetness, glycemic index, solubility and melting point, caloric content, which have the greatest influence on the organoleptic, technological and physiological parameters of sugar quality. When calculating the complex index of sugar substitutes, it was suggested to introduce three indicators: the heat dissolution, water activity and the degree of tolerance. According to the selected indicators, which values have been transformed into a 10-point scale, profilograms have been constructed. Formulas of calculating the complex quality index were developed taking into account the validating factors of each indicator determined by the Delphi method. The calculation of the complex index of sugars’ quality showed a significant advantage of tagatose and the expediency of its use in the manufacture of confectionery products. The calculation of the complex index of quality of sugar substitutes showed that the highest score was registered by erythritol, fact that determines the expediency of its use in the manufacture of confectionery products with dietary function. The calculation showed the following values of the complex index of sugars’ quality – sucrose, glucose, fructose, maltose, lactose, tagatose, trehalose: 0.53, 0.46, 0.72, 0.44, 0.26, 0.81, 0.44, 0.47 respectively, and sugar substitutes – sorbitol, xylitol, isomaltotol, maltitol, erythritol, lactitol: 0.34, 0.42, 0.37, 0.47, 0.86, 0. 37 respectively. The article describes the sorption-desorption properties of various groups of confectionery products using sugars and sugar substitutes.